New frontiers in the neuroscience of the sense of agency - David, Nicole (Frontiers in Human Neuroscience, 2012)
The sense that I am the author of my own actions, including the ability to distinguish my own from other people's actions, is a fundamental building block of our sense of self, on the one hand, and successful social interactions, on the other. Using cognitive neuroscience techniques, researchers have attempted to elucidate the functional basis of this intriguing phenomenon, also trying to explain pathological abnormalities of action awareness in certain psychiatric and neurological disturbances. Recent conceptual, technological, and methodological advances suggest several interesting and necessary new leads for future research on the neuroscience of agency. Here I will describe new frontiers for the field such as the need for novel and multifactorial paradigms, anatomically plausible network models for the sense of agency, investigations of the temporal dynamics during agentic processing and ecologically valid virtual reality (VR) applications.